Cannabis Use in First-Episode Psychosis: Associations with Symptom Dimensions and Sociodemographic Factors - Aziz Mohammad (Journal of Pakistan Psychiatric Society, 2026)
AbstractObjective:To determine sociodemographic and clinical predictors of cannabis use among patients with first-episode psychosis (FEP) admitted to a tertiary care psychiatric unit in Pakistan.Methods:This cross-sectional study was conducted at the Psychiatry Unit, Khyber Teaching Hospital, Peshawar, from January 2021 to December 2024. Consecutive inpatients with FEP and no prior antipsychotic exposure were assessed using a structured proforma for sociodemographic and clinical data. Symptom severity was measured with the Positive and Negative Syndrome Scale (PANSS). Binary logistic regression was applied to identify predictors of cannabis use.Results:Among 104 participants (77.9% male; mean age 23.4 ± 8.4 years), cannabis use was reported exclusively among males (28.4%). Unemployment and lower socioeconomic status significantly predicted cannabis use. Being employed (OR = 0.017, 95% CI [0.001–0.367]) or a student (OR = 0.064, 95% CI [0.006–0.693]) was associated with markedly lower odds of cannabis use compared with unemployment. Satisfactory socioeconomic status was also protective (OR = 0.074, 95% CI [0.010–0.522]). Clinically, moderate manic symptoms and higher PANSS activation scores were linked with lower likelihood of cannabis use (p < 0.05).Conclusion:Cannabis use in first-episode psychosis is strongly influenced by social determinants such as occupation and socioeconomic status rather than symptom severity. Culturally informed, gender-sensitive prevention strategies are needed to address substance use risk in psychosis within South Asian contexts.